Modern information policy: regional projection - A. M. Dudaev; I. V. Kryuchkov (Современная наука и инновации)
The present article examines modern approaches to the characterization of the information policy of the Russian Federation and its regional implementation in the Chechen Republic. The trends contributing to the formation of synergistically complex power are noted, including such factors as the "digital revolution" and "digital metamorphosis". The author analyzes the conditions under which the state can effectively and sustainably control the content and semantic component of the information space. The experience of regional information policy in the Chechen Republic reveals the typological and functional features of the Ministry of Information and Press of the Chechen Republic. The methods and approaches of modeling information policy in the regional context are considered, special attention is paid to the aspect of the management plan. The traditional specific regional features of the information policy of the Chechen Republic are revealed.